Hôm kia lúc 7:49

$a,\left|3x-2\right|=x$

$\left|3x-2\right|=\left\{{}\begin{matrix}3x-2khix\ge\dfrac{2}{3}\\-3x+2khix< \dfrac{2}{3}\end{matrix}\right.$

Với $x\ge\dfrac{2}{3}\Rightarrow3x-2=x\Rightarrow x=1$

Với $x< \dfrac{2}{3}\Rightarrow-3x+2=x\Rightarrow x=\dfrac{1}{2}$

Vậy $S=\left\{1;\dfrac{1}{2}\right\}$

$b,\left|x-1\right|=x^2-x-1$

$\left|x-1\right|=\left\{{}\begin{matrix}x-1khix\ge1\\-x+1khix< 1\end{matrix}\right.$

Với $x\ge1\Rightarrow x-1=x^2-x-1\Rightarrow-x^2+x+x-1+1=0\Rightarrow-x^2+2x=0$

$\Rightarrow\left[{}\begin{matrix}x=2\left(tm\right)\\x=0\left(ktm\right)\end{matrix}\right.$

Với $x< 1\Rightarrow-x+1=x^2-x-1\Rightarrow-x^2-x+x+1+1=0\Rightarrow-x^2+2=0$

$\Rightarrow\left[{}\begin{matrix}x=\sqrt{2}\left(ktm\right)\\x=-\sqrt{2}\left(tm\right)\end{matrix}\right.$

Vậy $S=\left\{2;-\sqrt{2}\right\}$

$c,\left|2-3x\right|=x^2-6x-2$

$\left|2-3x\right|=\left\{{}\begin{matrix}2-3xkhix\ge\dfrac{2}{3}\\-2+3xkhix< \dfrac{2}{3}\end{matrix}\right.$

Với $x\ge\dfrac{2}{3}\Rightarrow2-3x=x^2-6x-2\Rightarrow-x^2+3x+4=0$

$\Rightarrow\left[{}\begin{matrix}x=4\left(tm\right)\\x=-1\left(ktm\right)\end{matrix}\right.$

Với $x< \dfrac{2}{3}\Rightarrow-2 +3x=x^2-6x-2\Rightarrow-x^2+9x=0$

$\Rightarrow\left[{}\begin{matrix}x=9\left(ktm\right)\\x=0\left(tm\right)\end{matrix}\right.$

Vậy $S=\left\{4;0\right\}$

$d,\left|x^2-4\right|=x^2+x+1$

$\left|x^2-4\right|=\left\{{}\begin{matrix}x^2-4khix\ge\pm2\\-x^2+4khix< \pm2\end{matrix}\right.$

Với $x\ge\pm2\Rightarrow x^2-4=x^2+x+1\Rightarrow-x-5=0\Rightarrow x=-5\left(tm\right)$

Với $x< \pm2\Rightarrow-x^2+4=x^2+x+1\Rightarrow-2x^2-x+3=0$

$\left[{}\begin{matrix}x=1\left(tm\right)\\x=-\dfrac{3}{2}\left(tm\right)\end{matrix}\right.$

Vậy $S=\left\{-5;1;-\dfrac{3}{2}\right\}$

Bình luận (1)
Hôm kia lúc 8:00

a) |3x - 2| = 3x - 2 ⇔ 3x ≥ 2 ⇔ x ≥ 2/3

|3x - 2| = 2 - 3x ⇔  3x - 2 < 0 ⇔ 3x < 2 ⇔ x < 2/3

*) x ≥ 2/3 ta có:3

x - 2 = x

⇔ 3x - x = 2

⇔ 2x = 2

⇔ x = 1 (nhận)

*) x < 2/3 ta có:

2 - 3x = x

⇔ -3x - x = -2

⇔ -4x = -2

⇔ x = 1/2 (nhận)

Vậy S = {1/2; 1}

b) |x - 1| = x - 1 ⇔ x - 1 ≥ 0 ⇔ x ≥ 1

|x - 1| = 1 - x ⇔ x - 1 < 0 ⇔ x < 1

*) x ≥ 1, ta có:

x - 1 = x² - x - 1

⇔ x² - x - 1 - x + 1 = 0

⇔ x² - 2x = 0

⇔ x(x - 2) = 0

⇔ x = 0 (loại) hoặc x - 2 = 0

**) x - 2 = 0

⇔ x = 2 (nhận)

*) x < 1 ta có:

1 - x = x² - x - 1

⇔ x² - x - 1 - 1 + x = 0

⇔ x² - 2 = 0

⇔ x² = 2

⇔ x = -√2 (nhận) hoặc x = √2 (loại)

Vậy S = {-√2; 2}

c) |2 - 3x| = 2 - 3x ⇔ 2 - 3x ≥ 0 ⇔ -3x ≥ -2 ⇔ x ≤ 2/3

|2 - 3x| = 3x - 2 ⇔ 2 - 3x < 0 ⇔ x > 2/3

*) x ≤ 2/3 ta có:

2 - 3x = x² - 6x - 2

⇔ x² - 6x - 2 - 2 + 3x = 0

⇔ x² + 3x - 4 = 0

⇔ x² - x + 4x - 4 = 0

⇔ (x² - x) + (4x - 4) = 0

⇔ x(x - 1) + 4(x - 1) = 0

⇔ (x - 1)(x + 4) = 0

⇔ x - 1 = 0 hoặc x + 4 = 0

**) x - 1 = 0

⇔ x = 1 (loại)

**) x + 4 = 0

⇔ x = -4 (nhận)

*) x > 2/3 ta có:

3x - 2 = x² - 6x - 2

⇔ x² - 6x - 2 - 3x + 2 = 0

⇔ x² - 9x = 0

⇔ x(x - 9) = 0

⇔ x = 0 (loại) hoặc x - 9 = 0

**) x - 9 = 0

⇔ x = 9 (nhận)

Vậy S = {-4; 9}

d) |x² - 4| = x² - 4 ⇔ x² - 4 ≥ 0 ⇔ x² ≥ 4 ⇔ x ≥ 2 hoặc x ≤ -2

|x² - 4| = 4 - x² ⇔ x² - 4 < 0 ⇔ x² < 4 ⇔ -2 < x < 2

*) Với x ≥ 2 hoặc x ≤ -2, ta có:

x² - 4 = x² + x + 1

⇔ x² - 4 - x² - x - 1 = 0

⇔ -x - 5 = 0

⇔ -x = 5

⇔ x = -5 (nhận)

*) Với -2 < x < 2, ta có:

4 - x² = x² + x + 1

⇔ x² + x + 1 + x² - 4 = 0

⇔ 2x² + x - 3 = 0

⇔ 2x² + 2x - 3x - 3 = 0

⇔ (2x² + 2x) - (3x + 3) = 0

⇔ 2x(x + 1) - 3(x + 1) = 0

⇔ (x + 1)(2x - 3) = 0

⇔ x + 1 = 0 hoặc 2x - 3 = 0

**) x + 1 = 0

⇔ x = -1 (nhận)

**) 2x - 3 = 0

⇔ 2x = 3

⇔ x = 3/2 (nhận)

Vậy S = {-5; -1; 3/2}

Bình luận (1)

Các câu hỏi tương tự
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết
Xem chi tiết